Advanced Intelligent Computing Theories and Applications. With Aspects of Artificial Intelligence - De-Shuang, Huang (Springer, 2017)
The organizers of ICIC 2008, the including the Center for International Scientific Exchanges of the Chinese Academy of Sciences, Shanghai University, and the Insti-tute of Intelligent Machines of the Chinese Academy of Sciences, made an enor-mous effort to ensure the success of ICIC 2008. We hereby would like to thank the members of the ICIC 2008 Advisory Committee for their guidance and advice, and the members of the Program Committee and the referees for their collective effort in reviewing and soliciting the papers. We would like to thank Alfred Hofmann, Executive Editor at Springer, for his frank and helpful advice and guidance throughout and for his support in publishing the proceedings. In particular, we would like to thank all the authors for contributing their papers. Without the high-quality submissions from the authors, the success of the conference would not have VI been possible. Finally, we are especially grateful to the IEEE Computational Intel-ligence Society, the International Neural Network Society and the National Science Foundation of China for their sponsorship.